Cosmic ray ballon measurements at laow geomagnetic latitudes, september 1962 through 1958 - Ghielmetti, H.; Becerra, N.; Godel, A.M.; Heredia, H.; Marzulli, L.C.; Roederer, Juan (American Geophysical Union, 1964)
Fil: Ghielmetti, H. Comisión Nacional de Energía Atómica; Argentina